(ï³,ï´)- Strongly Derivations Pairs on Rings - Saed, I. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
Let R be an associative ring. In this paper we present the definition of (s,t)- Strongly derivation pair and Jordan (s,t)- strongly derivation pair on a ring R, and study the relation between them. Also, we study prime rings, semiprime rings, and rings that have commutator left nonzero divisior with (s,t)- strongly derivation pair, to obtain a (s,t)- derivation. Where s,t: RÂ®R are two mappings of R.